Pengaruh Struktur Modal, Pertumbuhan Perusahaan, Dan Kebijakan Dividen Terhadap Nilai Perusahaan (Jurnal Kendali Akuntansi, 2023)
this study aims to determine and analyze the effect of capital structure, company growth and dividend policy on firm value in manufacturing sector companies listed on the indonesia stock exchange. The population in this study are all manufacturing sector companies listed on the indonesia stock exchange during the 2017-2021 observation period is 80 companies. The number of samples in this study were 16 companies with a total of 80 observations. Sampling in this study using purposive sampling technique. This study uses secondary data obtained from the indonesian stock exchange website. Methods of data analysis using multiple linear regression and statistical t-test. The results of the study show that, capital structure has a positive and insignificant effect on company value. Company growth has a negative and insignificant effect on company value. Dividend policy has a significant positive effect on company.